2021
DOI: 10.1101/2021.05.04.442663
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 variant B.1.617 is resistant to Bamlanivimab and evades antibodies induced by infection and vaccination

Abstract: SUMMARYThe emergence of SARS-CoV-2 variants threatens efforts to contain the COVID-19 pandemic. The number of COVID-19 cases and deaths in India has risen steeply in recent weeks and a novel SARS-CoV-2 variant, B.1.617, is believed to be responsible for many of these cases. The spike protein of B.1.617 harbors two mutations in the receptor binding domain, which interacts with the ACE2 receptor and constitutes the main target of neutralizing antibodies. Therefore, we analyzed whether B.1.617 is more adept in en… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
79
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(82 citation statements)
references
References 60 publications
2
79
0
1
Order By: Relevance
“…India is facing a large surge in COVID-19 cases since early 2021. Many cases are caused by a new lineage, termed B.1.617 [1][2][3][4][5][6] . The epidemiology data are scarce, but B.1.617 has become the predominant strain in the state of Maharashtra and probably in other Indian regions 4 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…India is facing a large surge in COVID-19 cases since early 2021. Many cases are caused by a new lineage, termed B.1.617 [1][2][3][4][5][6] . The epidemiology data are scarce, but B.1.617 has become the predominant strain in the state of Maharashtra and probably in other Indian regions 4 .…”
Section: Introductionmentioning
confidence: 99%
“…
The SARS-CoV-2 B.1.617 lineage emerged in October 2020 in India [1][2][3][4][5][6] . It has since then become dominant in some indian regions and further spread to many countries.
…”
mentioning
confidence: 99%
“…We also identified seven patients with COVID-19 caused by B.1.617.1 or B.1.617.2, variants reported to be causing widespread disease and extensive public health concern in India. [43][44][45][46][47][48] In the aggregate, our genome data show that VOC and VOI now account for the great majority of all new COVID-19 cases in our region.…”
Section: [Introduction]mentioning
confidence: 63%
“…Actually, in their preprint work Hoffmann et al analyzed whether the SARS-CoV-2 VOC B.1.617 is more adept in entering cells and/or evade Ab responses. 85 They found that B.1617 entered two out of 8 cell lines tested (specifically, the human lung-and intestine-derived Calu-3 and Caco-2 cell lines, respectively) with slightly increased efficiency, and was blocked by an entry inhibitor. However, in stark contrast, B.1.167 was found to be fully resistant to LY-CoV555 and partially resistant against neutralization by Abs elicited upon infection or vaccination with the Comirnaty/Pfizer-BioNTech vaccine.…”
Section: δδGmentioning
confidence: 99%